ENTREPRENEURIAL INTENTIONS OF INDIAN UNIVERSITY STUDENTS: A FRAMEWORK OF INDIVIDUAL, CONTEXTUAL, AND EDUCATIONAL FACTORS - Raghavendra; Shivaprasad (International Journal of Research -GRANTHAALAYAH, 2024)
This study explores how universities in India can cultivate entrepreneurial potential among students, driving both innovation and economic growth. By developing a detailed framework, the research dives into the personal, contextual, and educational factors that inspire students' entrepreneurial intentions. It identifies self-efficacy, social networks, and structured entrepreneurship education as critical motivators, shedding light on how these elements collectively influence a student’s journey toward entrepreneurship. Using a thematic approach, the study pieces together insights from the literature, revealing that tailored educational programs, dedicated university support, and awareness of sustainability play powerful roles in equipping students with the skills and mindset needed for success. Social and cultural capital also stand out as key forces, creating support networks that can either fuel or dampen entrepreneurial ambitions. While the framework provides a valuable roadmap, it also highlights the need to adapt educational strategies to diverse cultural contexts, suggesting areas for future exploration. This work aims to inform educational practices and policies, ultimately contributing to a more vibrant entrepreneurial ecosystem. Through this integrated approach, the study offers new perspectives on how institutions can inspire and support the next generation of entrepreneurs, using education, social capital, and institutional resources as essential building blocks.